2023
DOI: 10.1186/s40337-023-00779-y
|View full text |Cite
|
Sign up to set email alerts
|

Medical instability in typical and atypical adolescent anorexia nervosa: a systematic review and meta-analysis

Abstract: This review investigates the relationship between weight and risk of medical instability (specifically bradycardia, hypotension, hypothermia, and hypophosphatemia) in adolescents with typical and atypical anorexia nervosa. Atypical anorexia nervosa, listed as an example under the DSM-5 category of Other Specified Feeding and Eating Disorders (OSFED), describes patients who are not clinically underweight but otherwise meet criteria for anorexia nervosa. There is a lack of empirical evidence exploring medical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Patients with atypical AN represent those who develop the eating disorder following less weight loss upon adjustment for age, height, illness duration, and premorbid weight. In combination with the lack of empirical support for clinically relevant differences in psychological and medical characteristics between diagnoses (Billman Miller et al, 2024;Brennan et al, 2023;Johnson-Munguia et al, 2024;Walsh et al, 2023), we interpret our findings as further support for a homogenous illness model. We believe this interpretation represents the most parsimonious explanation for currently available data.…”
Section: Diagnostic Separation Of An and Atypical Ansupporting
confidence: 67%
See 1 more Smart Citation
“…Patients with atypical AN represent those who develop the eating disorder following less weight loss upon adjustment for age, height, illness duration, and premorbid weight. In combination with the lack of empirical support for clinically relevant differences in psychological and medical characteristics between diagnoses (Billman Miller et al, 2024;Brennan et al, 2023;Johnson-Munguia et al, 2024;Walsh et al, 2023), we interpret our findings as further support for a homogenous illness model. We believe this interpretation represents the most parsimonious explanation for currently available data.…”
Section: Diagnostic Separation Of An and Atypical Ansupporting
confidence: 67%
“…The heterogeneous model of AN and atypical AN has notable shortcomings, including an extant research base illustrating generally similar psychological and medical characteristics in both illnesses (Brennan et al, 2023;Johnson-Munguia et al, 2024;Walsh et al, 2023). Thus, differentiating diagnoses with a 'significantly low body weight' has not been externally validated.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this study did not include measures of physiological symptomology. Existing studies have found that physiological symptoms or medical instability occur both among individuals with atypical AN and AN (Brennan et al, 2023;Sawyer et al, 2016). Future research should include such measures to more comprehensively identify potential differences among individuals with these diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…'underweight,' particularly in light of growing support for a homogenous illness conceptualization (e.g., Walsh et al, 2023), may inadvertently reinforce longstanding misconceptions about restrictive eating disorders (e.g., Harrop et al, 2021). Despite comparable and potentially life-threatening symptoms (Billman Miller et al, 2024;Brennan et al, 2023;Chew et al, 2023;Garber et al, 2019;Johnson-Munguia et al, 2024;Sawyer et al, 2016;Whitelaw et al, 2018;Zanna et al, 2021), individuals with atypical AN experience myriad treatment barriers compared to patients with AN, purportedly reflecting a society permeated with weightrelated stigma (Ali et al, 2017;Eiring et al, 2021;Harrop et al, 2021;Kastner et al, 2021;Kennedy et al, 2017;Kons et al, 2024). Historically, AN has been synonymized with 'underweight,' with patients described with 'extreme emaciation' or 'inanition' dating back to the mid-19th century (Gull, 1997;Lasègue, 1997).…”
Section: Ongoing Differentiation Of An and Atypical An Via Clinicalmentioning
confidence: 99%
“…Patients with atypical AN consistently demonstrate similar or more severe eating disorder psychopathology (Chew et al, 2023;Garber et al, 2019;Johnson-Munguia et al, 2024;Sawyer et al, 2016;Swenne, 2016), psychiatric comorbidities and associated impairment, quality of life, adverse life events, and suicidality compared to patients with AN (Billman Miller et al, 2024;Chew et al, 2023;Johnson-Munguia et al, 2024;Zanna et al, 2021). Youth with atypical AN also demonstrate similar medical sequelae to clinically 'underweight' patients with AN and require hospitalizations at a comparable rate (Brennan et al, 2023;Garber et al, 2019;Sawyer et al, 2016;Whitelaw et al, 2018).…”
mentioning
confidence: 93%